Implementation of Guided Inquiry Learning To Improve The Critical Thinking Skills of Junior High School Students (Journal of Innovative Science Education, 2019)
Science learning is expected to provide students with the provision to grow and improve critical thinking skills. Someone who has the ability to think critically can identify strategies and make the right decisions in problem solving. The results of previous studies indicate that junior high school students' critical thinking skills are in low category. This study aims to analyze the improvement of students' critical thinking skills through guided inquiry learning. Guided inquiry learning is one of innovative learning that is appropriately applied to science learning, because students can be actively involved in the learning process to search and investigate systematically with teacher guidance. The design of this study used quasi experiment with non-equivalent control group design. Students' critical thinking skills are measured using 27 multiple choices. The results showed that critical thinking skills of experiment group were higher than those control group and the improvement of students' critical thinking skills in aspects elementary clarification, basic support, inference, advanced clarification of experiment group higher than control group, while aspects strategy and tactics of experiment and control group have different increases in the same category.